G-protein modulation of ionic currents in cardiac myocytes - Goodstadt, L; Leo Goodstadt (2000)
The modulation of L-type calcium current (ICa) and the catecholamine-induced chloride current (ICl,cAMP) by G-protein coupled regulatory pathways were studied in isolated guinea pig cardiac ventricular myocytes using the whole cell patch clamp and flash photolysis techniques. A number of novel findings are reported in this thesis. The rapid release of GTP, the natural ligand of G-proteins, from its inert caged precursor produced a large enhancement of ICa which could be detected within 20 ms of the photolysing light pulse. A fast component of this response persisted under conditions of current rundown and inhibition of cAMP-dependent phosphorylation. This suggests the involvement of a membrane-delimited pathway not dependent on soluble second messengers. The photorelease of the non-hydrolysable GTPγS caused a biphasic increase in ICa in the majority of myocytes and a sustained response in the others. Pipette dialysis with GTPγS had a three-fold effect: pertussis toxin-sensitive inhibition of the ICa responses to isoprenaline, forskolin and photoreleased GTP; competitive inhibition of the enhancement of ICa by further photoreleased GTPγS; and modulation of the kinetics of cAMP-dependent activation of ICl,cAMP and ICa without any significant changes in their magnitudes. The flash photolysis of caged cAMP produced large increases in both ICl,cAMP and ICa but the latter was more than twice as sensitive to cAMP (EC50 = ~ 1.1 μM and ~ 0.47 μM). Urotensin has recently been identified as the ligand for a previously orphaned G-protein coupled receptor, and has been shown to be a potent chronic vasoconstrictor. This thesis reports an additional modulatory effect on ICl,cAMP. μM urotensin had no effect on its own but potentiated responses to sub-maximal sympathetic stimulation. Estrogen reduces forskolin- and isoprenaline-stimulated cAMP accumulation in the rat heart and inhibits cardiac ICa via a G-protein. However, the application of μM ß-estradiol to guinea pig myocytes in the presence of low doses of either forskolin (0.5 μM) or isoprenaline (20 nM) produced large increases in ICl,cAMP. This effect was mediated by a cell surface receptor. The involvement of nitric oxide synthase (NOS) was not required, unlike in acute estrogenic responses in vascular endothelia. Raloxifene, a selective estrogen receptor modulator (SERM), was similarly able to potentiate the results of sympathetic stimulation but with a much slower time course.